The relationship between different upper extremity patterns and independence level in individuals with spastic cerebral palsy from the ICF perspective - Bingöl, Hasan; Kocaman, Hikmet; Kerem Günel, Mintaze (Journal of Surgery and Medicine, 2020)
Aim: Although various upper limb and hand involvement patterns in individuals with cerebral palsy (CP) have been defined, our knowledge about their functionality in daily life is still insufficient. The purpose of this study was to investigate upper extremity involvement patterns concerning the level of functionality in individuals with spastic CP. Methods: A total of 101 individuals, aged 7 to 21 years, with spastic cerebral palsy (30% unilateral CP, 70% bilateral CP), and a total of 172 hand and upper limb patterns were evaluated in this study. To identify different spastic upper extremity patterns, two classification systems, one for the upper limb and one for the hand (Classification of Upper Limbs and Hand Patterns), were used separately. Then, the Manual Ability Classification System [MACS] and Functional Independency Measure [Wee-FIM] were utilized to quantify hand functions and functional independency level, respectively, in the activities of daily living. Results: A strong correlation was found between MACSI and Simple Flex of Hand Pattern (r=0.72) while a moderate correlation was detected between MACSII and Simple Flex of Hand Pattern (r2=0.57). Besides, the level of independence in daily living activities was consistent with Type Ia and Type Ic patterns of the upper limb (r1=0.56 and r2=0.44) Conclusion: It was concluded in the light of the obtained data that Type Ia and Type Ic patterns of the upper limb, as well as Simple Flex of the hand pattern, are very efficient for functionality. Additionally, the pattern of Simple Flex Plus and Intrinsic Punching Hand were significantly related to bad capacity in hand functioning. The various upper limb and hand patterns affect the functionality or functional independence in daily living. Consequently, abnormal upper limb and hand patterns, which commonly occur in the upper extremities of children with CP, are quite different from each other in terms of functionality. Hence, it is recommended that before the application of BoNT-A or orthopedic surgery in managing spasticity, the client should be comprehensively evaluated in both terms of rigidity and functionality.